Human activities recognition of the aged - Niu, Zhen (Nanyang Technological University, 2022)
With the high development of computing technology and sensor technology in recent years, they have been widely used in smartphones, and these technologies have made our cell phones move towards more intelligence. The popularity of smartphones has also reached an unprecedented level, which has greatly facilitated our lives.